LIVED EXPERIENCES OF PERSONS WITH VISUAL IMPAIRMENTS; A PHENOMENOLOGICAL APPROACH (Contemporary Journal of Social Science Review, 2025)
The present study aimed to explore the lived experiences of persons with visual impairments; focusing on how they perceive their disability and the coping mechanisms they adopt to manage daily life challenges in personal, educational, and social contexts. Despite increasing awareness of disability inclusion, individuals with visual impairments continue to face developmental, social, and educational barriers. A qualitative research design grounded in phenomenology was employed. Five participants with visual impairments were selected through purposive sampling from the Department of Special Education, Punjab. In-depth, semi-structured interviews were conducted to gather detailed narratives of their experiences. An interview guide was used to conduct semi-structured interviews, and data were analyzed using Interpretative Phenomenological Analysis (IPA) to identify themes and subthemes within participant narratives. Four superordinate themes emerged from the data: (1) awareness of disability, (2) adaptation to disability, (3) resilience and self-efficacy, and (4) the need for assistive devices. Participants demonstrated a high level of self-awareness, strong adaptive behaviors, emotional resilience, and a desire for independence. The study concludes that while individuals with visual impairments exhibit remarkable resilience and adaptability, their full potential is constrained by the absence of inclusive infrastructure and resources. The findings call for enhanced support through assistive technologies, inclusive educational practices, and awareness initiatives to ensure their equal participation in society.